Evaluating the Effectiveness of Online Training for a Comprehensive Violence Against Women Program: A Pilot Study. Issue 1 (January 2021) - Etherington, Cole; Baker, Linda; Ham, Marlene; Glasbeek, Denise
Evaluating violence against women (VAW) training is essential to moving the field forward with proven approaches that can improve service provision for survivors of violence. Given existing resource constraints involved in VAW work, online training represents an economical and flexible option; however, existing evaluations of online programs in the VAW field are scant and face a variety of limitations. This study aimed to fill this gap by using a pre-/posttest design, comparison group, and mixed-method analysis to assess the effectiveness and value of an online training program. The program was intended to provide foundational knowledge in feminist antiviolence principles and values to a range of individuals working with survivors of intimate partner violence (IPV). Program participants ( N = 108) included volunteers, students, and professionals from various sectors, allowing for the application of the results to a broader field of VAW support services. This is important as individuals who work with IPV survivors may do so in a range of settings outside of the shelter context. Results demonstrate the potential for online VAW training to improve participants' knowledge of and attitudes about VAW, which can positively inform their work with survivors. Qualitative responses provide further insight into course impact and highlight positive and negative aspects of the course. Although preliminary, these results provide justification for continued development and evaluation of online VAW training programs.